Change in biomarkers of type-2 inflammation following severe exacerbations of asthma. Issue 1 (18th July 2018) - Semprini, Ruth; Shortt, Nick; Ebmeier, Stefan; Semprini, Alex; Varughese, Rachel; Holweg, Cecile T J; Matthews, John G; Fingleton, James; Weatherall, Mark; Beasley, Richard; Braithwaite, Irene
Abstract : We investigated the time course of change of type-2 asthma biomarkers after a severe asthma exacerbation. Blood eosinophils were lowest immediately after treatment was initiated (0.07 vs 0.33×10 9 /L, p<0.001) while serum IgE levels were at their highest (339 vs 249 U/L, p<0.001). Fractional exhaled Nitric Oxide levels were lowest 2 weeks after treatment (23 vs 33 ppb, p=0.06) and serum periostin levels were lowest 1 week after treatment (45·9 vs 50·9 ng/mL, p<0.001). A delay of 4–8 weeks following a severe exacerbation is required if these biomarkers are used to guide the ongoing management of patients with asthma. Trial registration number: Post-results; The Australia New Zealand Trial Registry, >ACTRN12614000443695.